Vibrio gazogenes Inhibits Aflatoxin Production Through Downregulation of Aflatoxin Biosynthetic Genes in Aspergillus flavus - Shyam L. Kandel; Rubaiya Jesmin; Brian M. Mack; Rajtilak Majumdar; Matthew K. Gilbert; Jeffrey W. Cary; Matthew D. Lebar; Phani M. Gummadidala; Ana M. Calvo; Kanniah Rajasekaran; Anindya Chanda (PhytoFrontiers, 2022)
Aspergillus flavus is an opportunistic pathogen of oilseed crops such as maize, peanut, cottonseed, and tree nuts and produces carcinogenic secondary metabolites known as aflatoxins during seed colonization. Aflatoxin contamination not only reduces the value of the produce but is also a health hazard to humans and animals. Previously, we observed inhibition of A. flavus aflatoxin biosynthesis on exposure to the marine bacterium Vibrio gazogenes (Vg). In this study, we used RNA sequencing to examine the transcriptional profiles of A. flavus treated with both live and heat-inactivated dead Vg and control samples. Fungal biomass, total accumulated aflatoxins, and expression profiles of genes constituting secondary metabolite biosynthetic gene clusters were determined at 24, 30, and 40 h after treatment. Statistically significant reductions in total aflatoxins were detected in Vg-treated samples as compared with control samples at 40 h. However, no statistical difference in fungal biomass was observed on these treatments. The Vg treatments were most effective on aflatoxin biosynthesis, as was reflected in significant downregulation of most genes in the aflatoxin gene cluster, including the aflatoxin pathway regulator gene, aflR. Along with aflatoxin genes, we also observed significant downregulation in some other secondary metabolite gene clusters, including cyclopiazonic acid and aflavarin, suggesting that the treatment could inhibit other secondary metabolites as well. Finally, a weighted gene correlation network analysis identified an upregulation of 10 genes that were most strongly associated with Vg-dependent aflatoxin inhibition and provide a novel starting point in understanding the mechanisms that result in this phenomenon. [Figure: see text] The author(s) have dedicated the work to the public domain under the Creative Commons CC0 “No Rights Reserved” license by waiving all of his or her rights to the work worldwide under copyright law, including all related and neighboring rights, to the extent allowed by law, 2022.